Contamination of Cereals (Sorghum Bicolor L. Moench and Pennisetum Glaucum (L.) R. Br.) During Storage: Farmer’s Perception and Management of Mold’ Contamination Risks - Tovide, Noel; Tchobo, Fidele; Adeoti, Kifouli; Noumavo, Pacome; Baba-Moussa, Farid; Gandonou, Christophe; Toukourou, Fatiou (European Scientific Journal, ESJ, 2017)
This study aimed to report the traditional technics used in Benin to store sorghum and millet grains and assess the knowledge level of the farmers and sellers on the problematic of mold contamination during the grain storage. Entire sorghum and millet production areas were carried out. Face-to-face interview of 1,040 farmers and sellers of both cereals were conducted. The data were collected according to an adapted set of questions based on direct observation, group discussions, individual interviews and garret visits containing sorghum and millet. The results were analyzed using SAS software. The survey results provided by this approach showed that 93.24% of farmers were men and 100 % of sellers were women. 68.92% of farmers had over 50 years old while 64.29% of sellers had less than 35 years. Their education level was relatively low and marked by 70% of unlettered. Several storage technics are used. The most widely used is solar drying, but it has the lowest shelf life compared to the second widely used to apply the chemical pesticides to cereals product. According to them, this technic allows a long shelf life for the cereals. The most of interviewed farmers and sellers (69%) use moldy grains in animal feed while 11% used it in human consumption. 13 % of both cereals were destroyed and 7 % of them ignore that mold can have caused the sanitary risks. In view of the socio-economic importance of the cereals and their role in the nutritional needs of people it become necessary to trained the farmer and sellers in other drying and storage technics in order to prevent food-borne diseases.